Analisis Pengaruh Persepsi dan Pola Asuh Orang Tua terhadap Minat Melanjutkan Studi Akuntansi ke Perguruan Tinggi di SMK Gondanglegi dan Pagelaran - Mahmudah, Nufidatul (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2025)
Student’s interest to study further in university with accounting major commonly influenced by many factors, including externals and internals. This research’s objective is to analyze the influence of parents’ perceptive thoughts and their parenting style towards the students’ interest in accounting major. This research uses quantitative approaches and the population subjects are students in Gondanglegi and Pagelaran. Sampling techniques uses in this study is purposive sampling by questionnaire techniques in data collection. Data is analyzed using dobled-linear regression to get the relation between independent and dependent variables. Results of this study shows that student’s perceptions of accounting major positively and significantly influence their interest to study further for linear major. Besides that, parenting style negatively influences to student’s interest. This study implies that to increase student’s interest in accounting major or department, educational institutions should focus on quality development and teaching methods.